2015
DOI: 10.1161/strokeaha.115.010992
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Ischemic Stroke Among Young Adults

Abstract: We have recently presented a new method of assessing spatiotemporal resolved PM 2.5 and PM 10 exposures 18,19 in the Negev (South Israel)-a semi-arid area, located in the global dust belt, which extends from West Africa to the Arabian Desert. 20 Unlike many commonly used exposure models, our model makes use of satellite aerosol optical depth measurements, which allowed us to estimate daily, spatially resolved, PM 10 and PM 2.5 concentration with the inclusion of populations in rural areas not living nearby mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 44 publications
2
29
2
Order By: Relevance
“…As previously described for myocardial infarction, the risk was still increased at pollution levels below current European air quality standards [32]. Exposure to road traffic also increased the risk of stroke, with strong associations with ischaemic stroke observed in subjects living within 75 m of a main road [33]. Hourly or daily changes in pollutant concentrations were also related to an increased risk of stroke and stroke mortality, with a strong association between ultrafine particles and stroke mortality [34].…”
Section: Epidemiological Evidencementioning
confidence: 73%
“…As previously described for myocardial infarction, the risk was still increased at pollution levels below current European air quality standards [32]. Exposure to road traffic also increased the risk of stroke, with strong associations with ischaemic stroke observed in subjects living within 75 m of a main road [33]. Hourly or daily changes in pollutant concentrations were also related to an increased risk of stroke and stroke mortality, with a strong association between ultrafine particles and stroke mortality [34].…”
Section: Epidemiological Evidencementioning
confidence: 73%
“…Due to their small size, PM10 can penetrate human lungs and cause a wide variety of cardiopulmonary diseases (Figure 1.2) (Folinsbee, 1992;Pope and Dockery, 2006;WHO, 2006). Exposure to the pollutant can decrease lung function , aggravate diseases such as asthma (Whittemore and Korn, 1980;Choudhury et al, 1997) and ischemia (Bell et al, 2008;Yitshak-Sade et al, 2015), and raise the likelihood of developing lung cancer (Pope et al, 2002;Parent et al, 2007;. Studies have also linked maternal exposure to PM10 during pregnancy to adverse birth outcomes such as pre-term delivery (Ha et al, 2014), very pre-term delivery (Ha et al, 2014), and low birth weight (Chen et al, 2002;Dugandzic et al, 2006;Bell et al, 2007;Seo et al, 2010;Ha et al, 2014).…”
Section: Impacts Of Pm10 Pollutionmentioning
confidence: 99%
“…A larger study in Israel, also using satellite-derived measures of exposure, found no overall association between ischemic stroke and same-day PM 2.5 exposure, but did find marginally significant association among those <55 years of age in stratified models. 35 …”
Section: Discussionmentioning
confidence: 99%